The Qumran Rule Texts in Context: Collected Studies - Hempel, Charlotte (Texts and Studies in Ancient Judaism - Band 154, 2013)
Hauptbeschreibung: Ever since the discovery of the Dead Sea Scrolls the Community Rule has been at the forefront of the scholarly imagination and is often considered a direct channel to life on the ground at Khirbet Qumran - an ancient version of 'reality television'. After the full publication of the Dead Sea Scrolls one might legitimately have expected that the complete spread of evidence would present us with most of the answers that we have been looking for. Instead, scholars increasingly recognize the significance of the Scrolls as a rich text world from a period when texts, tra